2016
DOI: 10.1111/epi.13434
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol does not affect spasms in the betamethasone‐NMDA rat model of infantile spasms

Abstract: SUMMARYObjective: This study attempted to validate the effects of neonatal estradiol in ameliorating the spasms in the prenatally betamethasone-primed N-methyl-D-aspartate (NMDA) model of infantile spasms in rats as shown previously in a mouse Arx gene knock-in expansion model of infantile spasms. Methods: Neonatal rats prenatally exposed to betamethasone (on day 15 of pregnancy) were treated with subcutaneous 40 ng/g estradiol benzoate (EB) between postnatal days (P)3-P10 or P0-P5. A synthetic estrogen analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Our previous studies indicated that ACTH suppresses the occurrence of NMDA-triggered spasms in both sexes 20 , 24 . Here we show that the complement C5ar1 receptor antagonist, PMX53, also reduced spasms, suggesting contribution of the innate inflammatory system, represented by C5a, to IS.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our previous studies indicated that ACTH suppresses the occurrence of NMDA-triggered spasms in both sexes 20 , 24 . Here we show that the complement C5ar1 receptor antagonist, PMX53, also reduced spasms, suggesting contribution of the innate inflammatory system, represented by C5a, to IS.…”
Section: Discussionmentioning
confidence: 96%
“…1B ). Pups were treated with either ACTH (twice on P12 and three times a day on P13 and P14, each dose of 0.3 mg/kg sc; the effective treatment paradigm in our IS model) 20 , 24 , PMX53 (one daily dose of 0.6 mg/kg sc on P12, P13, P14 and P15; effective previously against seizure in epilepsy models) 10 or saline as control, on P12, P13, P14 and P15. Spasms were followed for 60 min after the trigger and latency to onset of spasms from the trigger and number of spasms was calculated during the observation period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this model, the efficacy of several compounds has been tested. In contrast to the Arx expansion model, neonatal 17β-estradiol failed to provide protection from NMDA-induced spasms [72]. The successful treatment of NMDA-induced spasms with ACTH and vigabatrin [73] suggests that both steroid hormones and GABAergic inhibition play a critical role in IS generation.…”
Section: Increased Glutamate Receptor Activation: Prenatal Stress/nmdmentioning
confidence: 90%
“…A recent report in the prenatal betamethasone/postnatal NMDA acute model of spasms also did not report any effects of 17β-estradiol early treatment (PN3-10) on NMDA spasms induced on PN12, PN13, and PN15 male and female rats [54]. We did not observe any differences in the developmental milestones or weights between 17β-estradiol or oil-treated male rats till PN13, although it was previously reported that weight gain is increased in estradiol-treated mixed male and female PN15 rats in the prenatal betamethasone/postnatal NMDA model [54]. In addition, the differences in species (mouse vs rats) and neurodevelopmental effects of the altered genetic background in ARX (GCG)10+7 mouse model may contribute to the differences in efficacy.…”
Section: Discussionmentioning
confidence: 99%